EVALUATION OF EXTERNAL QUALITY ASPECTS OF EGGS FROM FREE-RANGE INDIAN BREED CHICKENS FED WITH MILLET AND CORN GERM - Monteiro Filho, Flávio; Filgueira Maia, Wellington; Suede de Sousa Moura, Laila (Journal of Interdisciplinary Debates, 2023)
Getting to know alternative foods that keep the development of the quality of eggs, it is understood that the feeding of birds is very important for this process, given that meets the nutritional needs in all stages of production, optimizing the growth and its production efficiency, and can be influenced by factors such as management conditions, facilities, nutrition and environment. Given the above objective with this research analyzing the physical parameters of the egg through alternative food such as corn, millet and corn germ. The experiment was conducted at Farm Agua Viva in Luziânia-GO, where they were confined in a thirty laying shed Indian race with the same age, being subdivided by box, with different food. Although the care of raising chickens in any situation are considered, water control it is necessary, lighting, bed and balance, creating a suitable environment, it was observed by analyzing the confined birds and bibliographic reports that you can get quality production and low cost by replacing corn with millet and corn germ. The alternative power is rather an option that combines cost and benefit in relation to the production of eggs from hens Indian race.